1995
DOI: 10.1002/jcb.240570317
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid amplifies vasopressin‐induced phosphoinositide hydrolysis in aortic smooth muscle cells

Abstract: It has been reported that glucocorticoid modifies phosphoinositide (PI) hydrolysis stimulated by vasoactive agents in vascular smooth muscle cells. In the present study, we investigated the point at which glucocorticoid affects vasopressin-induced PI hydrolysis in primary cultured rat aortic smooth muscle cells. The pretreatment with dexamethasone significantly amplified the formation of inositol trisphosphate (IP3) induced by vasopressin in a dose-dependent manner in a range of 1 pM to 10 nM. The effect of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Cortisol potentiated NE-induced Ins(1,4,5)P 3 synthesis in both nonpregnant and pregnant uterine arteries. Glucocorticoid-mediated potentiation of Ins(1,4,5)P 3 production has been reported in vascular smooth muscle for angiotensin II, arginine vasopressin, endothelin-1, and catecholamines (24,30,43). The role of Ins(1,4,5)P 3 as the messenger of pharmacomechanical Ca 2ϩ mobilization in smooth muscle has been firmly established (35).…”
Section: Discussionmentioning
confidence: 96%
“…Cortisol potentiated NE-induced Ins(1,4,5)P 3 synthesis in both nonpregnant and pregnant uterine arteries. Glucocorticoid-mediated potentiation of Ins(1,4,5)P 3 production has been reported in vascular smooth muscle for angiotensin II, arginine vasopressin, endothelin-1, and catecholamines (24,30,43). The role of Ins(1,4,5)P 3 as the messenger of pharmacomechanical Ca 2ϩ mobilization in smooth muscle has been firmly established (35).…”
Section: Discussionmentioning
confidence: 96%
“…The elevation of mRNA levels precedes the rise in binding activity, suggesting a transcriptional effect. Furthermore, it has been reported that GC amplify the vasopressin-induced transduction signal (increased IP accumulation in the presence of dexamethasone) (312,313). At the protein level, GC have been shown to produce an early decrease in binding site density, followed later by an increase, which becomes more prevalent with time.…”
Section: A Tissue-specific Expression and Regulation Of Membrane Hormentioning
confidence: 99%
“…V1a receptor is located mainly in the central nervous system and cardiovascular organs including VSMC, while V1b and V2 are located in the central nervous system and kidney, respectively. As for intracellular signaling mechanisms, it has been reported that AVP mobilizes intracellular Ca 2+ and stimulates protein kinase C (PKC) through the activation of phospholipase (PL) C and PLD in VSMC [15][16][17], which is involved in the mechanism of AVP-induced proliferation of these cells [18]. Other important signaling pathways to mediate the mitogenic and differentiation processes are tyrosine kinases.…”
mentioning
confidence: 99%